Analisis Isu Kesehatan Mental Anak Pada Buku Cerita Bilingual Karya Arleen A. - Fitriani, Meiliana Nur; Pratiwi, Anggia Suci; Dewi, Rikha Surtika; Nugraha, Mohammad Fahmi (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2025)
This study aims to identify the representation of mental health values in bilingual storybooks written by Arleen A., intended for children aged 6 to 12 years. The method employed is qualitative content analysis, as outlined by Krippendorff, which is an interpretive technique used to uncover meaning within texts by tracing emerging themes, patterns, and messages. Data collection followed several steps: selecting relevant texts, repeated readings, coding narrative elements related to mental health, and categorizing themes based on indicators developed by Marie Jahoda, which were previously validated by experts in child psychology and education. The findings reveal that 70% of the stories reflect positive values of self-acceptance. However, only 20% of the stories demonstrate healthy emotional regulation, and just 10% depict empathy or the resolution of social conflicts. Furthermore, there were no explicit narratives addressing the issue of bullying in any of the stories analyzed. These results suggest that while bilingual storybooks hold potential as a medium for promoting children's mental health literacy, there is a significant need to strengthen the representation of more complex and contextual social-emotional issues. Enhancing these dimensions can better support children’s psychosocial development and equip them with the emotional and social skills necessary to navigate real-life challenges.